Local Stabilization for Multiple Input-Delay Systems Subject to Saturating Actuators: The Continuous-Time Case - Chen, Yonggang; Wang, Zidong; Shen, Bo; Han, Qing-Long (IEEE transactions on automatic control, 2022)
In this article, the local stabilization problem is dealt with for a class of continuous-time multiple input-delay systems subject to saturating actuators. Using the generalized sector conditions and the piecewise Lyapunov-Krasovskii functional, and carrying out rigorous mathematical deduction, a sufficient condition is established under which the closed-loop dynamics is exponentially stable for admissible initial conditions. Subsequently, the explicit characterization of controller gains is obtained in terms of the solvability of linear matrix inequalities. The special cases concerning the constant and single delays are also discussed. Moreover, optimization problems are proposed to maximize the estimate of the domain of attraction. Finally, two examples are given to show the effectiveness and advantages of the obtained results.